RETRACTED: Abnormal Plasma Levels of Steroids and Their Ratios in Patients With Prurigo Nodularis: A Pilot Study - Chu, Liuxi; Shu, Xin; Wu, Yan; Yang, Haoran; Lu, Qin; Deng, Huihua (Frontiers in Physiology, 2022)
Background: It has been suggested that cortisol levels are abnormal in chronic urticaria and atopic dermatitis, but other steroids, such as dehydroepiandrosterone (DHEA) and testosterone, are still unknown, and whether these hormones affect the maintenance of skin homeostasis or the pathogenesis of skin diseases is not fully understood. Limited data are available on steroid levels in prurigo nodularis (PN)-related research, and no study has examined the association between pruritus severity and steroid levels in PN patients. Aims: This pilot study aimed to investigate the differences in the levels of five steroids combined with their ratios in plasma between PN patients and controls and to examine the associations between the biomarkers and pruritus severity. Methods: Plasma concentrations of five steroids, including cortisol, cortisone, testosterone, progesterone, and dehydroepiandrosterone (DHEA), in 36 patients with PN were compared with concentrations in thirty-six and matched healthy controls. The concentrations of steroids were quantitated using liquid chromatography-tandem mass spectrometry. The PN symptoms, including pruritus severity, pain and life quality, were assessed with the use of the visual analog scale, prurigo score index, numerical rating scale, and verbal rating scale and dermatology life quality index scores. Results: In comparison with controls, PN patients had lower levels of plasma cortisol and cortisone, which negatively correlated with PN symptoms. PN patients had higher levels of cortisone and testosterone to cortisol, which positively correlated with pruritus severity. Additionally, there were no significant differences in plasma concentrations of DHEA and testosterone between the 2 groups. We found no correlation between plasma concentrations of DHEA and testosterone and pruritus severity. Conclusion: This pilot study suggests that there may be abnormalities in peripheral blood levels of cortisol, and cortisone and the ratios of cortisone and testosterone to cortisol in patients with PN, and they are related to pruritus severity. The plasma concentrations of testosterone and DHEA may be not abnormal in PN patients and may not be associated with pruritus severity.